The Scope and Limitations of Ternary Blend Organic Photovoltaics. Issue 3 (29th September 2014) - Savoie, Brett M.; Dunaisky, Scott; Marks, Tobin J.; Ratner, Mark A.
<x xml:space="preserve">Abstract</x> Ternary organic photovoltaic donor:acceptor blend active materials composed of three distinct species possess remarkable advantages over neat semiconductors and binary donor:acceptor blends. A blended semiconductor is a foreign concept for inorganic semiconductors, whereas electronically disparate organic semiconductors can be mixed while mutually enhancing the properties of each. This feature allows ternary semiconductors to realize many of the advantages of tandem solar cells in a single layer. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>